2016
DOI: 10.3310/hta20470
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of a randomised controlled trial of physiotherapy for adults with joint hypermobility syndrome

Abstract: BackgroundJoint hypermobility syndrome (JHS) is a heritable disorder associated with laxity and pain in multiple joints. Physiotherapy is the mainstay of treatment, but there is little research investigating its clinical effectiveness.ObjectivesTo develop a comprehensive physiotherapy intervention for adults with JHS; to pilot the intervention; and to conduct a pilot randomised controlled trial (RCT) to determine the feasibility of conducting a future definitive RCT.DesignPatients’ and health professionals’ pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(66 citation statements)
references
References 86 publications
1
62
0
Order By: Relevance
“…Often, it was not that a treatment had worked, but that healthcare professionals had taken the time to listen compassionately and empathetically to patients "rather than Invalidation can be a common problem with rheumatic diseases [41], and involves a lack of understanding or negative social responses from others, such as disbelief, rejection, stigmatization and suspicion that the problem may be psychological in origin [41]. In line with other examples within the literature, participants in this study experienced very long waits for diagnosis, allegations of hypochondria or malingering, and a lack of understanding and knowledge of the condition from healthcare professionals [12,13,15,42,43].…”
Section: Social Supportmentioning
confidence: 65%
“…Often, it was not that a treatment had worked, but that healthcare professionals had taken the time to listen compassionately and empathetically to patients "rather than Invalidation can be a common problem with rheumatic diseases [41], and involves a lack of understanding or negative social responses from others, such as disbelief, rejection, stigmatization and suspicion that the problem may be psychological in origin [41]. In line with other examples within the literature, participants in this study experienced very long waits for diagnosis, allegations of hypochondria or malingering, and a lack of understanding and knowledge of the condition from healthcare professionals [12,13,15,42,43].…”
Section: Social Supportmentioning
confidence: 65%
“…Education for health professionals [Billings et al, ; Rombaut et al, ; Terry et al, ; Lyell et al, ; Russek et al, ] is paramount in order to optimize physical therapy provision. A recent feasibility study of a six session package of treatment demonstrates future potential [Palmer et al, ,] and further research is required to explore the specific therapeutic actions of physical therapy for managing JHS/hEDS. Recently, a meta‐analysis revealed that for treatment of adults, a significant pain reduction was achieved by a variety of physical and cognitive approaches.…”
Section: Principles Of Management Of Individuals With Jhs/eds‐ht In Cmentioning
confidence: 99%
“…There has been recent interest in validating upper and lower limb assessment scales that account for a greater number of joints and planes of movement (Meyer, Chan, Hopper, & Nicholson, ; Nicolson and Chan, ) and it will be interesting to see if such scales can be incorporated into the diagnostic criteria in due course. Secondly, patients have reported that physiotherapists often only treat single joints in isolation, particularly if they have been referred with one particularly problematic joint (Palmer et al, ). It is clear that such a reductionist approach to management is unlikely to be successful and a much more holistic approach is required that considers the biomechanical relationships between body areas and addresses psychosocial factors.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of knowledge and understanding of the condition has meant that assessment and treatment of JHS patients has been problematic. Both health professionals and patients have expressed a need for JHS to be treated holistically, as often only a single aspect or single joint is considered (Palmer et al, ). People with JHS present with such a wide array of signs and symptoms that they cannot be treated with one singular intervention (Malfait et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation